ANALISIS PERBANDINGAN TOTAL BIAYA PERSEDIAAN ANTARA KEBIJAKAN PERUSAHAAN DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) PADA PT LCG - Tessa Handra; Shibyl Rangian (STIE Wiyatamandala, 2017)
Inventory is one of important factor that should be considered in operational management. In operational management, in order to achieved efficiency, then firm resources should be manage and alocate base on its priority and its impact. Inventory Cost will affect Total Cost of Production, so when its not properly manage it will cost the firm. As long as the cost remain low, the firm will achieve low cost production to create competitive advantages over the competitor. EOQ or Economic Order Quantity has been taught in many university as simple inventory model. The idea is quite simple and its goal is to achieve minimum Total Cost of Production base on the efficiency between carrying cost and ordering cost. We conducted research about EQO in LCG Corporation. LCG Corporation produce clothes and sell it to many Indonesia market. Their segment is for kids. Our challenge is to adapt and applied EOQ to their inventory. Before this research LCG face many problem regarding to efficiency in inventory management. This research hope could help LCG problem and give solution to achieve minimum Production Cost.